ANALISIS TINGKAT KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DAN KUALITAS PELAYANAN DI RESTORAN CEPAT SAJI McDONALD’S CABANG ROBINSON, DENPASAR - Jentrasaswin, Gede Paramananda; Wiranatha, A.A.P. Agung Suryawan; Satriawan, I Ketut (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 2 (2018): AprilDO - 10.24843/JRMA.2018.v06.i02.p04, 2018)
Product quality and services have been the most concern of the trade and service. One of the efforts that can be used to improve and maintain the competitiveness of a company is to increase consumer satisfaction. The objectives of this study were 1) to determine the level of consumer interest in the products and services provided by McDonald’s, 2) to analyze the performance of McDonalds company in giving satisfaction to consumer, and 3) to analyze the level of customer satisfaction on products and services. Data collection in this study was done by distributing 255 questionnaires to consumers. Importance Performance Analysis method was used to analyse the effect of quality of the product & service on consumer satisfaction. The results show that consumers were satisfied on the product quality and service provided. The level of consumer satisfaction was 84,64% (satisfied) for the product quality and 83,06% (satisfied) for the service quality. Keywords:  Costumer satisfaction, importance performance analysis, McDonald’s